2016
DOI: 10.4049/jimmunol.1501675
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Regulates the Homeostasis of Tissue-Restricted Innate-like T Cells

Abstract: Although Notch signaling plays important roles in lineage commitment and differentiation of multiple cell types including conventional T cells, nothing is currently known concerning Notch function in innate-like T cells. We have found that the homeostasis of several well-characterized populations of innate-like T cells including invariant NKT cells (iNKT), CD8ααTCRαβ small intestinal intraepithelial lymphocytes, and innate memory phenotype CD8 T cells is controlled by Notch. Notch selectively regulates hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In another study, RORγt + ILCs near the marginal zone were shown to stimulate marginal zone B cells via production of B cell-activation factor (BAFF), co-stimulatory receptor ligand CD40L and DLL1 (45), providing an evidence of crosstalk between innate and adaptive immune system. Lastly, T-cell specific Notch1/2 deletion as well as FRC-specific ( Ccl19 -Cre) DLL1 or DLL4 deletion led to severe reduction, both in number and in function, of hepatic invariant NKT (iNKT) cells, CD8ααTCRαβ small intestinal intraepithelial lymphocytes and innate memory phenotype CD8 T cells, providing another line of evidence that Notch signaling is indispensable for innate-like T cells differentiation and function (46). …”
Section: Notch Signaling In Immune Cell Differentiation and Functionmentioning
confidence: 99%
“…In another study, RORγt + ILCs near the marginal zone were shown to stimulate marginal zone B cells via production of B cell-activation factor (BAFF), co-stimulatory receptor ligand CD40L and DLL1 (45), providing an evidence of crosstalk between innate and adaptive immune system. Lastly, T-cell specific Notch1/2 deletion as well as FRC-specific ( Ccl19 -Cre) DLL1 or DLL4 deletion led to severe reduction, both in number and in function, of hepatic invariant NKT (iNKT) cells, CD8ααTCRαβ small intestinal intraepithelial lymphocytes and innate memory phenotype CD8 T cells, providing another line of evidence that Notch signaling is indispensable for innate-like T cells differentiation and function (46). …”
Section: Notch Signaling In Immune Cell Differentiation and Functionmentioning
confidence: 99%